2021
DOI: 10.1523/jneurosci.1654-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Interneurons as Gatekeepers to Neuroplasticity after Injury or Disease

Abstract: Spinal interneurons are important facilitators and modulators of motor, sensory, and autonomic functions in the intact CNS. This heterogeneous population of neurons is now widely appreciated to be a key component of plasticity and recovery. This review highlights our current understanding of spinal interneuron heterogeneity, their contribution to control and modulation of motor and sensory functions, and how this role might change after traumatic spinal cord injury. We also offer a perspective for how treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 149 publications
0
48
0
Order By: Relevance
“…They integrate descending motor commands and sensory input from primary afferent fibers to modulate motor neuron activity and motor output [88,89]. There are diverse subpopulations of segmental spinal interneurons, many of which have been discovered in the context of understanding the neural control of locomotion and have been reviewed extensively elsewhere [90][91][92][93][94][95][96][97][98][99]. Long projecting propriospinal interneurons that connect cervical and lumbar enlargement are also important for interlimb coordination, especially during locomotion [100].…”
Section: Plasticity In Spared Descending Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…They integrate descending motor commands and sensory input from primary afferent fibers to modulate motor neuron activity and motor output [88,89]. There are diverse subpopulations of segmental spinal interneurons, many of which have been discovered in the context of understanding the neural control of locomotion and have been reviewed extensively elsewhere [90][91][92][93][94][95][96][97][98][99]. Long projecting propriospinal interneurons that connect cervical and lumbar enlargement are also important for interlimb coordination, especially during locomotion [100].…”
Section: Plasticity In Spared Descending Systemsmentioning
confidence: 99%
“…Interneurons in the cervical cord are involved in many tasks, such as breathing, locomotion, and reach-to-grasp [97,[105][106][107][108]. An example of propriospinal interneurons involved in the reach are the V2a interneurons, which relay information between motoneurons and the cerebellum to provide an 'internal feedback loop' [109].…”
Section: Plasticity In Spared Descending Systemsmentioning
confidence: 99%
“…In contrast, in eleven brain regions, notably the gigantocellular reticular nucleus, the red nucleus, the pedunculopontine nucleus, and the pontine central grey, regression slopes differed significantly from zero with R values that varied between 0.75 and 0.93 at different timepoints. Interestingly, the number of spared propriospinal neurons in cervical spinal cord, counted in cleared tissue between C2 and C6, also correlated well with functional recovery, highlighting the potential importance of cervical neurons as a supralumbar control center (R=0.83, slope<0 p=.0018, simple linear regression) ( Supplemental Figure 8 ) (Zholudeva et al, 2021). Overall, these data support the utility of whole-brain imaging and quantification to partially explain variability in functional outcomes after spinal injury.…”
Section: Resultsmentioning
confidence: 94%
“…These changes can also refine and prune synaptic connections and promote the recruitment of other neurons (e.g., spinal interneurons) into the neural network ( Rank et al, 2015 ; Sandhu et al, 2015 ; Streeter et al, 2017 ). Spinal interneurons (SpINs) are a vital component of neuroplasticity ( Zholudeva and Lane, 2018 ; Zholudeva et al, 2021 ), that can change their pattern of activity and are reported to alter their connectivity to contribute to novel anatomical pathways. Most importantly, this neuroplastic potential can be therapeutically driven by either electrical stimulation or ABTs ( Harkema, 2008 ; van den Brand et al, 2012 ; Houle and Cote, 2013 ).…”
Section: Methods To Enhance Plasticitymentioning
confidence: 99%